Anotasi atas Peraturan Presiden Nomor 87 Tahun 2017 tentang Penguatan Pendidikan Karakter - Fazal Akmal Musyarri (Jurnal Hukum Lex Generalis, 2020)
The discourse regarding the mature arrangement of Character Education came to the fore in recent times. This is because academic education has not even though it affects intelligence but does not necessarily build the character of a human being. At this point, character education is needed that not only supports academic needs but also the nature and character so that the government through the Ministry of Education and Culture of the Republic of Indonesia begins to develop a character education system that is spelled out through the national education system and applied in Nusantara schools. Normatively, the regulation on Character Education is contained in Presidential Regulation No. 87 of 2017 on Strengthening Character Education. In this paper will be discussed the implementation of Character Education and its effectiveness adapted to the essential thinking of Ki Hadar Dewantara.